2018
DOI: 10.1007/s12551-018-0454-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of H3O+ on the membrane morphology and hydrogen bonding of a phospholipid bilayer

Abstract: At the 2017 meeting of the Australian Society for Biophysics, we presented the combined results from two recent studies showing how hydronium ions (HO) modulate the structure and ion permeability of phospholipid bilayers. In the first study, the impact of HO on lipid packing had been identified using tethered bilayer lipid membranes in conjunction with electrical impedance spectroscopy and neutron reflectometry. The increased presence of HO (i.e. lower pH) led to a significant reduction in membrane conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
1
12
0
1
Order By: Relevance
“…The role of pH on the structure and dynamics of membrane lipids has been investigated on membrane model systems. Studies reported that low pH enhances membrane thickness, influences spontaneous curvature and induces head group protonation 40,41 . However, when cells are adapted to grow at low pH, only the external leaflet must adapt physically to an elevated H þ concentration, whereas the rest of the cell membranes must adapt to support this growth condition without being directly exposed to low pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of pH on the structure and dynamics of membrane lipids has been investigated on membrane model systems. Studies reported that low pH enhances membrane thickness, influences spontaneous curvature and induces head group protonation 40,41 . However, when cells are adapted to grow at low pH, only the external leaflet must adapt physically to an elevated H þ concentration, whereas the rest of the cell membranes must adapt to support this growth condition without being directly exposed to low pH.…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol quantitative analysis was performed as previously described 41 . Briefly, an aliquot of fraction B was first derivatized with a mixture of bis-trimethylsilyltrifluoroacetamide (BSTFA): pyridine (4:1 v/v) for 30 min at 60 C, and then injected into a gas chromatograph-mass spectrometer (GC-MS, Varian Saturn 2100).…”
Section: Cholesterol Analysismentioning
confidence: 99%
“…2), with the outer interface serving, hypothetically, mostly as a shield to avoid proton loss to the bulk phase. In this sense, a recent report using molecular dynamics suggests that the H 3 O + ions resided within the inner zone for longer periods associated with the carbonyl groups of the ester bond more than with any of the oxygens of the phosphates [33]. However, this data should be taken with caution given that the technique cannot actually model the bond breakage that iLPT would require.…”
Section: Practical Advantage Of Ester Lipidsmentioning
confidence: 98%
“…The self-assembly of the membranes relies primarily on the hydrophobic interactions of lipid molecules and proteins. The hydrophobic core can form spontaneously in water, forming the basis of the biological membrane self-assembly system [49][50][51][52]. Among these, cubic membranes, discovered in various intracellular membranes of different life forms, deserve specific attention.…”
Section: Biological Bicontinuous Cubic Structuresmentioning
confidence: 99%